Impact of restoration thickness and tooth shade background on the translucency of zirconia laminate veneers: An in vitro comparative study - Carlos A. Jurado; Abdulaziz Alhotan; Salwa Mekled; Seok-Hwan Cho; Kelvin I. Afrashtehfar (Saudi Dental Journal)
Purpose: Our in vitro comparative study aimed to investigate the impact of thickness and tooth shade background on the translucency of highly translucent zirconia veneers. Materials and Methods: A total of 75 5Y-TZP zirconia veneers of shade A1 were fabricated with thicknesses of 0.50 mm (n = 25), 0.75 mm (n = 25), and 1.0 mm (n = 25). The translucencies were measured on composite resin teeth with shades A1, A2, A3, A3.5, and A4 using a digital color imaging spectrophotometer. Data were analyzed using ANOVA and post hoc Tukey’s test (p < 0.05). Results: The translucency values were optimal for the veneers placed over the substrate teeth with shades A1 and A2, regardless of the veneer thickness. Additionally, veneers with a thickness of 0.50 mm exhibited significantly higher translucency than those with thicknesses of 0.75 mm and 1.0 mm. Conclusions: Our study demonstrated that the translucency of the highly translucent zirconia veneers was influenced by both veneer thickness and tooth shade background. The optimal veneer thickness for achieving the highest translucency was 0.50 for the veneers with A1 and A2 shades placed over the substrate teeth. Clinical Relevance: The optimal thickness for achieving the highest translucency of the highly translucent zirconia laminate veneers was 0.50 mm for the veneers with A1 and A2 shades placed over the substrate teeth. Clinicians and dental technicians could consider this when selecting materials for aesthetic restorations.